2017
DOI: 10.1148/radiol.2016161225
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma: Comparison of RENAL Nephrometry and PADUA Scores with Maximum Tumor Diameter for Prediction of Local Recurrence after Thermal Ablation

Abstract: Purpose To evaluate the performance of the radius, exophytic or endophytic, nearness to collecting system or sinus, anterior or posterior, and location relative to polar lines (RENAL) nephrometry and preoperative aspects and dimensions used for anatomic classification (PADUA) scoring systems and other tumor biometrics for prediction of local tumor recurrence in patients with renal cell carcinoma after thermal ablation. Materials and Methods This HIPAA-compliant study was performed with a waiver of informed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 32 publications
(30 reference statements)
2
15
1
1
Order By: Relevance
“…Katsanos et al [33] and Rivero et al [34] have published meta-analyses on T1 RCC comparing ablation to surgery concluding that ablative therapies are associated with a lower complication rate and cause less of a decrease in eGFR compared with PN. These meta-analyses concerned all cT1 renal masses [35] without segregating T1a from T1b. More recently, Yu et al [36] found that there were no significant differences regarding oncologic outcomes and complications between percutaneous microwave ablation and laparoscopic partial nephrectomy for patients with cT1a renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Katsanos et al [33] and Rivero et al [34] have published meta-analyses on T1 RCC comparing ablation to surgery concluding that ablative therapies are associated with a lower complication rate and cause less of a decrease in eGFR compared with PN. These meta-analyses concerned all cT1 renal masses [35] without segregating T1a from T1b. More recently, Yu et al [36] found that there were no significant differences regarding oncologic outcomes and complications between percutaneous microwave ablation and laparoscopic partial nephrectomy for patients with cT1a renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…88 Another study, which included 207 patients treated with TA, proposes that maximum tumor diameter is superior to scoring systems in the prediction of local recurrence following ablation. 89 As TA outcomes continue to improve with comparable outcomes to PN, cost will likely play a larger role in the management of small RCCs. 90 A systematic review and meta-analysis identified six articles published from 2008 to 2013 that evaluated cost for the management of small renal masses.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be explained by the lack of a high complexity group in our study whereas the Camacho et al study had 61 low, 26 medium and 14 high patients regarding the RNS and the Schmit et al study had 351, 330 and 70 low, medium and high complexity cases respectively. On the other hand, Maxwell et al studied 217 biopsy-proven SRMs treated mainly with CT guided percutaneous RFA reporting that maximum tumor diameter was the strongest predictor of local recurrence with a Harrell C index = 0.81 while RNS was found to be significantly predictive but showing poor performance with a Harrell C index = 0.68, limiting its overall utility in the authors’ opinion [29]. Neither pathology report nor subtype of RCC were associated with recurrence nor mortality, which is consistent with previous research, finding that 64–84% of SRM are indolent tumors.…”
Section: Discussionmentioning
confidence: 99%